Putting Higher Education to Work : Skills and Research for Growth in East Asia - World Bank (World Bank, 2012)
A fundamental question facing East Asia, especially its low- and middle income economies, is how to sustain or even accelerate the growth of recent decades. From 1950 to 2005, for example, the region's real income per head rose sevenfold. With aging populations, these economies will need to derive an increasing share of growth from productivity improvements rather than from physical factor accumulation to drive growth. The book argues that higher education is failing to deliver skills for growth and research for innovation because of widespread disconnects between higher education institutions and other skill and research users and providers. These disconnects undermine the very functioning of the higher education system. The main assumption of the report is that to deliver labor market skills to higher education graduates, these institutions: (a) must have characteristics that are aligned with what employers and employees need; and (b) must be well connected among themselves and other skills providers. Similarly, to deliver research that can enhance innovation and productivity, higher education institutions need to have a strong role in research provision and have strong links with firms and other research providers.